Training For The Preparation of Financial Statements By Using Microsoft Excel For Students of SMK Muhammadiyah 9 Jakarta - Hariyani, Reni; Retnoningrum, Eny; Prasetio, Tio (Jurnal Abdimas Ekonomi dan Bisnis, 2022)
The preparation of financial reports follows the development of Information and Communication Technology (ICT) in today's digital era. The availability of various features and formula formulas that are presented in spreadsheet form in Microsoft Excel can help in completing the accounting cycle process. This training was given before the Covid-19 pandemic hit Indonesia. The training participants were students of the XI class of Accounting Department Muhammadiyah 9 Vocational High School (SMK) Jakarta. The problem that exists in the partner's place is that the development of ICT has not been optimally utilized in teaching and learning activities in the field of accounting. The methods provided in this training are by giving lectures and practical methods in operating Microsoft Excel to compile financial reports. The purpose of this Community Service activity is to provide practical knowledge in using Microsoft Excel to compile a company's financial statements. The result of the implementation of this training activity is that students can compile general journals, ledgers, trial balances and financial reports using Microsoft Excel. Participants have benefited greatly from this training in making financial reports using Microsoft Excel faster, easier, more accurate and efficient.